PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI BERBASIS METAKOGNITIF UNTUK MELATIHKAN KEJUJURAN SISWA - Yasir, Mochammad; Ibrahim, Muslimin; Widodo, Wahono (Universitas Negeri Surabaya, 2016)
The purpose of this research is produce Biology learning material based on metacognitive that valid, practical, and effective to practice reflective thinking skill. The development of learning material use the 4-D model and try out to do in class X 1 and X-2 of SMAN 1 Driyorejo second semester in academic year 2014/2015. Design of try out is One-Group Pretest-Posttest Design. The method of collecting data used document, observation, validation, test, and quetionnaires. The data analysis techniques used descriptive analysis of quantitative and qualitative. The results of this research are: 1) learning material developed has a valid category; 2) learning material in terms implementation of lesson plans category in feasibility and the activities of students according to the steps of metacognitive learning strategies with STAD cooperative model; and 3) the effectiveness of learning material in terms of: (a) improving student aspect of knowledge learning outcomes visible from the n-gain score with high category; (b) the completeness honesty of students respectively by 82.64% and 86.11% with the good category; c) the students responds toward material and implementation of learning positive. The conclusion is acquired from the results of this research show that the learning material based on metacognitive are proper valid, practical, and effective to practice reflective thinking skills of student. Tujuan penelitian ini untuk menghasilkan perangkat pembelajaran Biologi berbasis metakognitif yang valid, praktis, dan efektif untuk melatihkan kejujuran siswa. Pengembangan perangkat pembelajaran menggunakan model 4-D dan uji coba dilakukan di kelas X-1 dan X-2 SMAN 1 Driyorejo semester genap tahun ajaran 2014/2015 dengan rancangan penelitian One-Group Pretest-Posttest Design. Pengumpulan data menggunakan metode dokumen, observasi, validasi, tes, dan angket. Teknik analisis data menggunakan analisis deskriptif kuantitatif dan kualitatif. Hasil penelitian menunjukkan: 1) perangkat pembelajaran yang dikembangkan berkategori valid; 2) perangkat pembelajaran ditinjau dari keterlaksanaan RPP berkategori praktis dan aktivitas siswa sesuai pada tahap-tahap strategi belajar metakognitif dengan model kooperatif tipe STAD; dan 3) keefektifan perangkat pembelajaran ditinjau dari: (a) peningkatan hasil belajar aspek pengetahuan siswa terlihat dari n-gain dengan kategori tinggi; (b) ketuntasan kejujuran siswa masing-masing sebesar 82,64% dan 86,11% dengan kategori baik; dan (e) respon siswa terhadap perangkat dan pelaksanaan pembelajaran positif. Simpulan yang diperoleh dari hasil penelitian menunjukkan bahwa perangkat pembelajaran berbasis metakognitif yang dikembangkan layak valid, praktis, dan efektif untuk melatihkan kejujuran siswa